Wire + arc additive manufacturing for high-speed flight. - James, William Sean (Cranfield University, 2023)
The use of Wire + Arc Additive Manufacturing (WAAM) to manufacture high- speed projectiles, such as missiles, is currently an industry challenge due to the nature of high-speed flight and the extreme environment that components are exposed to. Alloys that are suitable for high-speed flight are creep resistant superalloys, this is due to the aggressive heating environment experienced by objects in high-speed flight, and the need for performance at extremely high temperatures. These materials are currently expensive and difficult to manufacture, which is less than ideal for non-recoverable systems such as airborne weapons. The development of missile systems requires flight tests to be affordable and operate in quick succession, to which rapid prototyping offers a significant advantage. The use of traditional manufacturing methods and supply- chain for this purpose are logistically challenging and expensive, mainly due to loss of material though machining. The use of WAAM in a rapid prototyping capability is the driver for this research. To be able to use the process to manufacture and prototype components for high-speed applications, would, if possible, be an excellent solution to reducing the amount of time and money that it currently costs to flight-test and develop these systems. WAAM could also be used for final design production. The effect WAAM route has on the high temperature properties of superalloys is largely unknown. This research is therefore focused on the development of the WAAM process, and selection of alloys suitable for high-speed flight and for WAAM deposition. Four creep-resistant superalloys underwent deposition using a plasma WAAM process and the resulting material was characterised to understand how WAAM affects high temperature performance. The research also investigates post-deposition heat-treatment of these alloys and develops parameters for inter-pass machine hammer peening to improve material performance. The findings from this project increases the understanding between the WAAM process and superalloy strengthening mechanisms and develops a method to increase the performance of additive manufactured material. The most appropriate alloys for both WAAM and the high-speed flight application were ranked and down selected based on their anticipated performance and weldability. The selected alloys then underwent extensive testing from room temperature to 1000 °C, to understand the performance of WAAM built structures at high temperature. The microstructure is examined throughout and found key differences between solid-solution strengthened and age hardened alloys which effects performance. Finally, in-process machine hammer peening was investigated for age hardened Rene 41 and found to greatly increase the performance to match that of the wrought material.
Keywords: Additive manufacturing; WAAM; Rene 41; Haynes 188; Inconel 718; Inconel 625; heat-treatment; mechanical properties; microstructure; fractography; machine hammer peening